2020
DOI: 10.1063/1.5126149
|View full text |Cite
|
Sign up to set email alerts
|

Modeling hydrodynamics, magnetic fields, and synthetic radiographs for high-energy-density plasma flows in shock-shear targets

Abstract: Three-dimensional FLASH radiation-magnetohydrodynamics (radiation-MHD) modeling is carried out to study the hydrodynamics and magnetic fields in the shock-shear derived platform. Simulations indicate that fields of tens of Tesla can be generated via Biermann battery effect due to vortices and mix in the counter-propagating shock-induced shear layer. Synthetic proton radiography simulations using MPRAD and synthetic X-ray image simulations using SPECT3D are carried out to predict the observable features in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…A variation on the beamlet technique is to use an object (such as a mesh, mask, or pepperpot) to subaperture the proton beam into many beamlets (Sokollik et al, 2008;Johnson et al, 2022), down to a few "pencil" beamlets (Lu et al, 2020), or even just down to a single beamlet (Chen et al, 2020). This allows one to probe areas of specific interest in a limited fashion that is more easily detectable (in terms of deflection) or to streak the beamlet in time.…”
Section: Meshes and Gridsmentioning
confidence: 99%
See 3 more Smart Citations
“…A variation on the beamlet technique is to use an object (such as a mesh, mask, or pepperpot) to subaperture the proton beam into many beamlets (Sokollik et al, 2008;Johnson et al, 2022), down to a few "pencil" beamlets (Lu et al, 2020), or even just down to a single beamlet (Chen et al, 2020). This allows one to probe areas of specific interest in a limited fashion that is more easily detectable (in terms of deflection) or to streak the beamlet in time.…”
Section: Meshes and Gridsmentioning
confidence: 99%
“…II.C.3. When this is done, successful measurements of electromagnetic fields in dense plasma can be made: Romagnani et al (2019) used qTrace particle-tracing simulations that included a scattering model to successfully diagnose the time evolution of fastelectron-induced current filaments in dielectric foams, while Lu et al (2020) showed that, provided that scattering was included in supporting particle-tracing simulations, magnetic fields generated by the Biermann battery at a shocked shear layer in a dense foam could be observed. Particle-tracing simulations of proton beams that have been performed using full particle-in-cell (PIC) codes (Huntington et al, 2015) are capable of including another physics effect (albeit one that is usually not important): the beam's feedback on the electromagnetic fields being imaged via collisionless interaction mechanisms.…”
Section: Particle-tracing Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Starting from initial surface roughness, signatures of 3D self-similar turbulent evolution were measured [174]. Complementary experiments at subscale laser energy have also evidenced self-generated magnetic fields by turbulence of the order of tens of teslas [175].…”
Section: Turbulent Hydrodynamics For Laboratory Astrophysics and Fundamental High-energy-density Hydrodynamicsmentioning
confidence: 99%